Aging Modulates the Hemispheric Specialization during Word Production - Hoyau, Elena; Boudiaf, Naila; Cousin, Emilie; Pichat, Cedric; Fournet, Nathalie; Krainik, Alexandre; Jaillard, Assia; Baciu, Monica (Frontiers in Aging Neuroscience, 2017)
Older adults exhibit normal accuracy in performing word retrieval and generation (lexical production; e.g., object naming) but they are generally slower (longer response times) than younger adults. To maintain this accuracy, older adults recruit compensatory mechanisms and strategies. We focused on two of such possible compensatory mechanisms; one semantic and one executive. These mechanisms are reflected at inter- and intra-hemispheric levels by various patterns of reorganization of cerebral networks for lexical production. Hemispheric reorganization changes were also evaluated in related to increase naming latencies. By means of fMRI, we examined 27 healthy participants (from 30 to 85 years) during an object naming task. We explored and identified patterns of cerebral reorganization elicited by this task. We report two main results. First, we revealed a pattern of reorganization at the intra-(left)-hemispheric level, the LAPA (Left Anterior-Posterior Aging) effect which consists of supplementary activation of left posterior (temporo-parietal) regions in older adults, with asymmetric activation along the left fronto-temporal axis. This pattern suggests that older adults recruit more semantic regions (posterior) to perform object naming. The second pattern consisted of bilateral recruitment of frontal regions in maintaining appropriate response times, especially in older adults who were faster performers. This pattern is discussed in terms of compensatory mechanism. We suggest that aging is associated with multiple, co-existing compensation and reorganization mechanisms and patterns during a lexical production task.